AB1186 THE NHS SCOTLAND THERAPEUTIC DRUG MONITORING SERVICE FOR BIOLOGIC MEDICINES: PRELIMINARY ANALYSIS OF UTILISATION AND CLINICAL RESULTS AT YEAR 1. (2nd June 2020) - Macdonald, J.; Perry, M.; Galloway, P.; Seenan, J. P.; Dunlop, A.
Abstract : Background: Anti-tumour necrosis factor α (anti-TNFα) drugs infliximab (IFX) and adalimumab (ADL) are effective treatments for several rheumatic diseases. Therapeutic drug level and anti-drug antibody monitoring (TDM) has emerged as a useful tool for optimising drug effectiveness, by identifying individuals who may benefit from dose or treatment frequency adjustment, or have secondary drug failure due to immunogenicity. Objectives: Ensuring safe and effective use of biologic medicines has been identified as a key priority for NHS Scotland. Inequity and inconsistency of access to TDM across the nation was recognised as a barrier to delivering best practice and so a nationally commissioned TDM service was proposed in January 2018 to support clinical practice, providing universal access to TDM for services treating inflammatory diseases across Scotland. Data collection and analysis of results regarding usage and clinical impact of the service were identified as key outcome measures to assess service success and sustainability. Methods: A service webpage was developed to provide guidance on testing strategies and interpretation of TDM results (1). An automated search of clinical data and test results recorded within the clinical biochemistry electronic results management system was conducted to identify all TDM tests performed between 01/01/2018 and 31/12/2018. Descriptive analysis outcomes included the number of samples received, processed, overall testing population, service utilisation by Health Board, number and results of TDM tests performed per patient. TDM results were interpreted according to published guidance on the service webpage and comparison was made with previously published data (2). Results: 3609 specimens were received for testing, from 13 of the 14 Scottish Health Boards. 3561 drug level (DL) tests were performed; 1786IFX, 1775 ADL. 2717 total antidrug anti-body (TABT) tests and 681 free antidrug anti-body tests (FABT) were performed according to service protocol. 2791 individuals had one or more TDM tests during the 12-month period, of whom 541 were tested twice or more (range 2-5). Conclusion: TDM has been enthusiastically embraced. It is estimated that > 50% of individuals treated with IFX or ADL have been tested at least once in the first year. DL results were found to be similar to previously published data, as were rates of antibody positivity. The large volume of data generated by the service may provide additional evidence regarding the utility of TDM in predicting clinical response. Next steps are to conduct a comparative effectiveness analysis where proactive vs reactive TDM testing strategies will be compared, with the primary outcome measure being the proportions of patients with secondary loss of response. References: [1]Scottish Biologic therapeutic Drug Monitoring Service https://www.nhsggc.org.uk/about-us/professional-support-sites/biochemistry/biological-therapy-monitoring/ [2]Jani, M. Et al (2015), Clinical Utility of Random Anti–Tumor Necrosis Factor Drug–Level Testing and Measurement of Antidrug Antibodies on the Long-Term Treatment Response in Rheumatoid Arthritis. Arthritis & Rheumatology, 67: 2011-2019. doi:10.1002/art.39169 Acknowledgments: Biogen GmbH contributed partial funding for this research. Authors had full editorial control and approval of all content Disclosure of Interests: Jonathan MacDonald: None declared, Martin Perry Grant/research support from: Grifols, Abbvie, Sandoz unrestricted educational grant, Consultant of: Abbvie, Gilead, Celltrion Advisory Board, Speakers bureau: Sandoz, Peter Galloway: None declared, John-Paul Seenan: None declared, Alan Dunlop: None declared